Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-05-29T13:24:10+02:00
P(x)-(x-1)(x+2)(x-1) tak zostało podane w zadaniu ale powinno być tak
P(x)=(x-1)(x+2)(x-3) prawda??

W(x)=P(x)Q(x)+R(x)
P₁(x)=x-1 i R₁(1)=5
P₂(x)=x+2 i R₂(-2)=2
P₃(x)=x-3 i R₃(3)=27

P(x)=(x-1)(x+2)(x-3) i R(x)=ax²+bx+c bo stopień R(x) musi być mniejszy niż stopień P(x)

podstawiamy
{R(1)=a+b+c=5
{R(-2)=4a-2b+c=2
{R(3)=9a+3b+c=27

{a+b+c=5
{4a-2b+c=2 /*(-1)
{9a+3b+c=27

{a+b+c=5
{-4a+2b-c=-2
{9a+3b+c=27

{-3a+3b=3 /:3
{5a+5b=25 /:5

{-a+b=1
{a+b=5

2b=6
b=3

a+3=5
a=2

2+3+c=5
5+c=5
c=0

{a=2
{b=3
{c=0

R(x)=2x²+3x
1 5 1